Analysis of Public Procurement of Medicines in Russia - PRODANOVA, Natalia Alekseevna (2021)
One of the main components of the drug supply of the country's population with medicines is public procurement, which at the legislative level implements the principle of universal access to medical care and guarantees the quality of medical services provided. The authors analyzed the system of public procurement of medicines in Russia: the main sources of financing, customers and suppliers, territorial distribution, structure of methods of placing state orders are determined.